Understanding South Korea's Poor Nation Brand Image: A Content Analysis Of Two Leading German Print News Media, 1948–2013 - Tim , Yung; Schwekendiek, Daniel (Penerbit Universiti Sains Malaysia (USM Press), 2015)
Despite the spectacular rise of South Korea's economy, the West continues to perceive it as an underdeveloped nation. To ferret out the macrohistorical causes of this perception, we perform a content analysis of Korea-related articles since 1948 in two leading German news weeklies. We find that South Korea's image has somewhat improved, transformed from that of the backward "Land of the Morning Calm" to that of a nation ranking among the most technologically advanced. However, certain images, such as "unstable," "unsafe" and "corrupt" persist, despite the fact that economic and political conditions have dramatically improved. Our research tentatively suggests that a systematic, long-term bias against South Korea in German print media accounts in part for its negative image there. However, the fact that this bias has recently abated suggests that those media will eventually produce a credible portrait of this far-away country